Green building and energy efficiency application decisions in sustainable project management - Saraçoğlu, Niyazi Mete. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Being traditionally one of the main drivers of social and economic development of a country, the construction industry is also a major contributor to the negative impacts on environment especially due to signifcant consumption of energy and resources over the lifecycle of a building and the associated green house gas emissions. Although a lot of e orts are put in place over the last two decades to develop and to promote green building practices and sustainability measures within the industry to minimize negative impacts, the industry is still facing di culties to adapt to this paradigm shift, especially in emerging markets. Therefore actual steps towards ensuring such shift yet remains as a major challenge. Within this context, this study aims to identify the critical stage for taking the decision to implement green building practices during the construction of a project while analysing in detail related decisions in order to give more visiblity to the decision makers' with regards to the degree of green building practices achievable over the construction stages depending on the timing of the decision from a sustainable project mangement perspective. In order to collect the necessary data, a survey is conducted with green building professionals and a case study is performed on three hospital projects in Turkey. While preferably such decision should be given as early as possible in the process for new constructions, it was found that the latest stage to give such decisions is early construction stage, beyond which the e orts put in place have little in uence on the outcomes.
Keywords: Sustainable buildings.; Buildings -- Energy consumption.